2017
DOI: 10.4314/as.v15i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Utilization potentials of lablab (<i>Lablab purpureus</i> (L.) Sweet) and the constraints of field pests and diseases in Nigeria

Abstract: In the last one decade and half, lablab was evaluated for its crop-livestock production potentials in Samaru, Kano and Benin City in both the savanna and humid forest zones of Nigeria. Very early, early and intermediate accessions were identified that may be suitable for dry savanna and late growing season of the humid forest while late, very late and extremely late accessions were identified for moist savanna and humid forest. Vegetable-type, grain-type and dual-purpose lablab were identified. Lablab grain ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Most of the interviewed participants utilize lablab as food in their households. Ewansiha et al (2016a) reported that farmers were adopting lablab as food due to its nutritional value. Similar findings have been reported ( Kankwatsa, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the interviewed participants utilize lablab as food in their households. Ewansiha et al (2016a) reported that farmers were adopting lablab as food due to its nutritional value. Similar findings have been reported ( Kankwatsa, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…High yields directly relate to more income for the farmers and hence, improved standards of living. Market preference ( Morrison, 2019 ), good cook ability ( Kankwatsa, 2018 ; Morrison, 2019 ), and forage quality ( Ewansiha et al, 2016a ) are other important attributes that require intensive research and be tailored to meet farmers’ selection criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research on lablab has primarily focused on animal feed (Ewansiha et al 2017 ) and soil conservation (Whitbread et al 2011 ) resulting in genetic erosion and a reduced gene pool in Africa, despite the crop's importance for food and nutritional security (Minde et al 2020 ). During the 1930s, studies on land use management in Tanzania's northern region reported the cultivation and production of lablab.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, Lablab purpureus, Centrosema pubescens and Stylosanthes guianensis are some of the available forage legumes for animal nutrition. In addition, forage legumes are multipurpose crop that are capable of improving soil fertility and protecting the soil (Ewansiha et al, 2016). Priority in the adoption of forage legumes for cultivation as feed for animals, are the need to evaluate the yield potential of such legumes, determine their adaptation and G x E interaction in different agro-ecology zones, and assessment of traits that can be used in improving biomass yield.…”
Section: Introductionmentioning
confidence: 99%